2019
DOI: 10.1016/j.ijpharm.2019.118547
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based mathematical modelling of solute transport within the epidermis and dermis

Abstract: The stratum corneum is the main barrier to transdermal drug delivery which has previously resulted in mathematical modelling of solute transport in the skin being primarily directed at this skin layer. However, for topical treatment and skin toxicity studies, the concentration in the epidermis and dermis is important and needs to be modelled mathematically. Hitherto, mathematical models for viable skin layers typically simplified the clearance of solute by blood, either assuming sink condition at the top of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…This work showed that convection could dominate axial dermal and deeper tissue transport for the highly plasma protein bound corticosteroids (3) and non-steroidal anti-inflammatory drugs (4). However, dermal capillary loops should also be considered in optimising viable skin modelling as we and others have shown using capillary models (1,2,7). In particular, we found that convectional transport in the dermal capillaries has a profound effect on the time course of dermal drug concentrations, including the time taken to reach a steady state concentration (1).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This work showed that convection could dominate axial dermal and deeper tissue transport for the highly plasma protein bound corticosteroids (3) and non-steroidal anti-inflammatory drugs (4). However, dermal capillary loops should also be considered in optimising viable skin modelling as we and others have shown using capillary models (1,2,7). In particular, we found that convectional transport in the dermal capillaries has a profound effect on the time course of dermal drug concentrations, including the time taken to reach a steady state concentration (1).…”
Section: Introductionmentioning
confidence: 54%
“…While systemic toxicity in this case is determined by the flux of the substance though the skin into the systemic circulation, and is relatively well studied, the skin toxicity after topical application depends on the substance concentration at reactive skin sites. This concentration, in turn, is dependent on the flux of solute through the stratum corneum, clearance from those sites and, where the target site is the superficial dermis, drug transport in the dermal tissues (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dermis could also play a role in drug transport and drug retention during transdermal delivery [50]. Previous works modeled the dermis (1) as an additional depot in which drugs can be stored [51]; (2) as an additional layer in which only diffusion and no drug removal by the blood flow was modeled [52]; (3) by adding a sink condition to the system [53]; (4) by modeling simplified capillary loops in the dermis [54]. An even more realistic model of dermis would require modeling the patient's blood flow since capillaries and vessels are present in the papillary and reticular dermis, respectively.…”
Section: Figure 2 3d and 1d Geometrical Models Of Square-shaped Drugmentioning
confidence: 99%
“…The dermis could also play a role in drug transport and drug retention during transdermal delivery (Menczel and Maibach, 1970). Previous works modeled the dermis 1) as an additional depot in which drugs can be stored (Heikkinen et al, 2015); 2) as an additional layer in which only diffusion and no drug removal by the blood flow was modeled (Manitz et al, 1998); 3) by adding a sink condition to the system (Grassi et al, 2011); 4) by modeling simplified capillary loops in the dermis (Calcutt and Anissimov, 2019). An even more realistic model of dermis would require modeling the patient's blood flow since capillaries and vessels are present in the papillary and reticular dermis, respectively.…”
Section: Continuum Model For Transdermal Fentanyl Deliverymentioning
confidence: 99%